Merleau-Ponty : space, place, architecture - Locke, Patricia M.; McCann, Rachel (Series in Continental thought ;, 2015)
"Phenomenology has played a decisive role in the emergence of the discourse of place, now indispensable to many disciplines in the humanities and social sciences, and the contribution of Merleau-Ponty's thought to architectural theory and practice is well established. Merleau-Ponty: Space, Place, Architecture is a vibrant collection of original essays by twelve eminent philosophers who mine Merleau-Ponty's work to consider how we live and create as profoundly spatial beings. The resulting collection is essential to philosophers and creative artists as well as those concerned with the pressing ethical issues of our time. Each contributor presents a different facet of space, place, or architecture. These essays carve paths from Merleau-Ponty to other thinkers such as Irigaray, Deleuze, Ettinger, and Piaget. As the first collection devoted specifically to developing Merleau-Ponty's contribution to our understanding of place and architecture, this book will speak to philosophers interested in the problem of space, architectural theorists, and a wide range of others in the arts and design community"--